The Digital Enchantment of Drottningholm - Sauter, Willmar (Nordic Theatre Studies, 2018)
How can we relate to a historical playing culture? In this essay, a counter-factual visit to the palaces and parks of Drottningholm outside Stockholm is presented. By means of digital technologies, this World Heritage Site could be animated with historical figures from the eighteenth century, thus giving a living picture of past playing. Even though such an encounter with the past is fully possible from a technical point of view, the realization of this project poses a number of practical and theoretical questions: How can the picture of eighteenth-century court life be broadened to include social perspectives of class, gender and ethnicity? What artistic decisions have to be taken to visualize the activities around the park and in the palace? What forms of interactions provided by the technology are suitable for various groups of visitors? Some answers to these questions are hinted at in this essay, but the general question of a poetics of playing remains in the abyss between the historical period and the contemporary access to it. Neither Friedrich von Schiller’s treatise on the aesthetic education of man nor Emanuel Kant’s rational view of judgment bridge the gap of historical distance. Could Hans-Georg Gadamer’s idea of the melting of historical horizons ever become a reality in the experiences of future visitors? Eventually, this project might only provide some pleasures of a poetry of playing.